Pengolahan Limbah Botol Plastik Dan Pemulihan Trauma Anak Pasca Gempa - Ardiansah, Defri; Putra, Satria Yosa; Wati, Kurnia Rahma; Aristina, Selvin; Anggraini, Sentri; Afriani, Ririn; Nur’aini, Hesti; Fariadi, Herri (Jurnal Gotong Royong, 2025)
This study aims to process plastic bottle waste into a medium for making a garden to reduce the accumulation of plastic waste in RT 58, Betungan Village, and provide an approach to post-earthquake trauma recovery by studying together and interactively to children in RT 58. This study uses an observational methodology involving residents, children in RT 58, and the local government. The findings show that the large pile of plastic bottle waste behind the RT 58 housing and polluting the surrounding environment can be used as a medium for a toga garden to add to the beauty of the environment in RT 58. The methodology for post-earthquake trauma recovery in children using the method of studying together and interactively increases courage and is one of the efforts to reduce children's trauma after the Bengkulu earthquake.